решите пожалуйста...аааа( завал

(lg x)^2-lg x=2; x>0; lg x=t; t^2-t-2=0; D=(-1)^2-4*1*(-2)=9=3^2; t_1=frac{-(-1)-3}{2*1}=-1; t_2=frac{-(-1)+3}{2*1}=2; lg x=-1; x_1=10^{-1}=0.1; lg x=2; x_2=10^2=100

 

3^{2x-3}-8*3^{x-2}=3; 3^{2x}*3^{-3}-8*3^x*3^{-2}=3; |*27 3^{2x}-24*3^x-81=0; (3^x-27)(3^x+3)=0; 3^x+3>0; 3^x-27=0; 3^x=27; 3^x=3^3; x=3

 

log_2 x-log_x 4=3; x>0; x neq 1; log_2 x- log_x 2^2=3; log_2 x-2 log_x 2=3; log_2 x-frac{2}{log_2 x}-3=0; frac{log^2_2 x-3log_2 x-2}{log_2 x}=0; log^2_2 x-3log_2 x-2=0; log_2 x=t; t^2-3t-2=0; D=(-3)^2-4*1*(-2)=17; t_1=frac{3-sqrt{17}}{2}; t_2=frac{3+sqrt{17}}{2}; x_1=2^{frac{3-sqrt{17}}{2}}; x_1=2^{frac{3+sqrt{17}}{2}};

 

log_2 (5x-1)-frac{3}{log_2 (5x-1)-1}+1=0; 5x-1>0; x> 0.2; log_2 (5x-1)-1=t neq 0; t+1-frac{3}{t}+1=0; t-frac{3}{t}+2=0; t^2+2t-3=0; (t+3)(t-2)=0; t_1=-3; t_2=2; log_2 (5x-1)-1=-3; log_2 (5x-1)=-2; 5x-1=2^{-2}; 5x-1=0.25; 5x=1.25; x_1=0.25; log_2 (5x-1)-1=2; log_2 (5x-1)=3; 5x-1=2^3; 5x-1=8; 5x=9; x_2=1.4

 

5^x-6*5^{-x}=3.8; |*5^x; 5^{2x}-3.8*5^x-6=0; 5^x=t>0; t^2-3.8t-6=0; D=(-3.8)^2-4*1*(-6)=38.44=6.2^2; t_1=frac{3.8-6.2}{2*1}<0; t_2=frac{3.8+6.2}{2*1}=5; 5^x=5; 5^x=5^1; x=1

Оцени ответ

Загрузить картинку